Valoración económica para optimizar el uso turístico de la cascada de Chapawanki de la provincia de Lamas, Región San Martín - Ruiz Lozano, Angelli Ludomilia (2016)
The aim of this research was to determine the economic value of the Chapawanki cascade located in Lamas town, in order to optimize the use of the tourist resort of the waterfall and estimate the willingness to pay (WTP) that visitors-tourists give to the changes in the welfare that produces them in the modifying of the environmental benefit which allows to determine the economic potential and optimizes the tourist use of the natural resource of the study. The contingent valuation method was used in this investigation, the economic value of the environmental benefits and services non-market goods represented by the Chapawanki waterfall area. Consequently, 179 surveys were made to visitors- tourist and with the application of the contingent valuation method the monetary value that users give to the recreational and tourist use of the Chapawanki cascade was estimated, with the willingness to pay to a change of quality S/ 12.73 per visitor-tourists a year, this value reflects the economic benefit associated with the tour recreation, and in order to develop a quality tourism is necessary to preserved and kept in good condition this natural resource. In this sense, this study permited to identify that estimates of welfare measures show a positive probability of willingness to pay by the visitors-tourists, these results should justify the implementation by the government authorities of financing projects shared with the community and businesses